MILLAH IBRAHIM AS AN EPISTEMOLOGICAL FOUNDATION FOR INTERRELIGIOUS HARMONY - Moh. Shofiyuddin (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2022)
This study analyzes the concept of millah Ibrahim in Tafsir al-Misbah by M. Quraish Shihab and reconstructs it as an epistemological foundation for interreligious harmony. Employing a qualitative library research approach with a hermeneutic-contextual exegesis framework, the primary data were derived from Tafsir al-Misbah on Qur’anic verses containing the phrase millata Ibrāhīm, supported by secondary literature on Qur’anic exegesis and religious pluralism. The findings reveal that millah Ibrahim forms a structured epistemological framework consisting of tawhid as a metaphysical foundation, fitrah as an anthropological basis, justice as a normative principle, and moderation as a practical orientation. This framework positions harmony not merely as a socio-political agenda but as an epistemological consequence of an inclusive theological consciousness. The study contributes to thematic Qur’anic studies and strengthens the discourse on religious moderation grounded in the Qur’an within Indonesia’s plural society.